An Interpretation on Automated 3D Printer Controlled Using Internet of Things (IoT) - K. Mayandi, P. Sethu Ramalingam, Selva Ganapathy K, Srivathsan N, Vasanth M (International Journal of Control and Automation, 2020)
Over a last decade, great strides have been in improving the quality and performance of 3D printing. This experiment is to control a 3D printer by using IoT devices. In this prototype, the user sends the 3d model to the cloud server. Then everything becomes automated. A Microcontroller automatically downloads the files and sends it to the slicing software. This software converts the 3D model into G-code. Then, the IoT device (e.g. raspberry in this case) sends these G-code to the 3D printer and the model is printed. Through this, the 3D printer can be automated, and hence it can have accessed from anywhere just by connecting it through the internet. Using this multiple 3D printer can be accessed and queued. The present work deals with the 3D printing with the help of the Internet of Things using various configurations. The prototype model of 3D printer using the Internet of Things is designed, fabricated, assembled, and finally carried out the tests for the performance. In addition, multiple 3D printers can be connected and 3d models can be printed using queueing mechanism.